Investigation of the antimicrobial properties of the R-type pyocins of Pseudomonas aeruginosa and the role of lasR in their expression - Oluyombo, Olubukola (2016)
Pseudomonas aeruginosa is an opportunistic pathogen responsible for a number of different human infections, and is the leading cause of mortality in cystic fibrosis (CF) patients. P. aeruginosa infections are difficult to treat due to a number of antibiotic resistance mechanisms and its propensity to form multicellular biofilms. It also uses a complex quorum sensing (QS) signalling mechanism to regulate virulence, but mutants in a key QS regulator (LasR) are often prevalent in CF clinical strains. Different strains of P. aeruginosa compete to dominate infections and one way they achieve this is to produce chromosomally encoded bacteriocins, called pyocins. The major classes of pyocins are the soluble (S-types) and the tailocins (R- and F-types). This study investigated the distribution of six S-type and three major groups of R-type pyocins in CF clinical isolates and their roles during strain interactions. Competition assays between strain pairs in both planktonic and biofilm modes of growth were performed between clinical strains and corresponding R-pyocin deletion mutants. Each clinical strain produced one R-pyocin but the distribution of S-pyocins was random. R-pyocins were central to strain dominance as evidenced by the reversal of competitive advantage in null-R-pyocin mutants both in planktonic and biofilm states. R-pyocins also demonstrated novel anti-biofilm activities. Genomic analysis of the most competitive strain (A026) showed that it is a lasR mutant, phylogenetically related to Liverpool Epidemic Strains (LES). Promoter fusion assays to study R-pyocin gene expression showed an increase in the expression of R-pyocin genes in a lasR mutant of PAO1 compared to the wild type. This LasR-linked pyocin expression was RecA-independent. Overall these findings establish the crucial role of R pyocins in P. aeruginosa strain competition and a link between QS and R-pyocins.